Sosialisasi Sediaan Serta Label Obat Ispa Dan Diare Terhadap Upaya Meningkatkan Pengetahuan Siswa Kelas 8i Di SMP Negeri 1 Grogol Sukoharjo Tahun 2014 - Erlina Candra Sari; Susi Endra Wati (Indonesian Journal on Medical Science, 2013)
ABSTRACT: Background:The societyâ€™s tendency to buy free-, limited-free or limited drugs sold in pharmacy is worried to result in adverse effect when it is not based on the sufficient knowledge of drug. To anticipate such the error, socialization was conducted on the Acute Respiratory Tract Infection and Diarrhea drug preparation and label to the 8I graders of SMP Negeri 1 Grogol Sukoharjo.Objective: This research aimed to find out the use of socialization with lecturing method in the learning process to improve knowledge viewed from the cognitive and affective learning outcomes of the 8I graders.Method: This study was a quantitative analitic observational with cross sectional consisting of two cycles. Each cycle consisted of four stages: planning, acting, observing and reflecting. The subject of research was the 8I graders. Data was obtained through unstructured interview, questionnaire and cognitive questions. Technique if analyzing data used was descriptive qualitative one.Result: The research showed that the socialization with lecturing method could improve: 1) cognitive learning outcome classically with the mean achievement of 72% in cycle I increasing to 80% in cycle II or with the percentage class passing of 71% in cycle I increasing to 100% in cycle II; 2) the affective learning outcome with the percentage achievement of 76% in cycle I increasing to 79% in cycle II.Conclusion: Socialization with lecturing method could improve the knowledge of the 8I graders of SMP Negeri Grogol Sukoharjo, viewed from the cognitive and affective learning outcomes of students.Keywords: Cross sectional, preparation and label of Acute Respiratory Tract Infection and diarhea drugs, affective and cognitive learning improvement.Â ABSTRAK: Latar Belakang:Kecenderungan masyarakat membeli obat bebas, obat bebas terbatas atau obat keras yang dijual di apotek dikawatirkan akan merugikan bila tidak dilandasi pengetahuan tentang obat yang cukup. Mengantisipasi kesalahan tersebut diadakan sosialisasi sediaan serta label obat ISPA dan diare terhadap siswa kelas 8I SMP Negeri 1 Grogol Sukoharjo.Tujuan:Penelitian untuk mengetahui penggunaan sosialisasi metode ceramah dalam proses pembelajaran untuk meningkatkan pengetahuan ditinjau dari hasil belajar kognitif dan afektif siswa kelas 8I.Metode:Penelitian ini merupakan Penelitian kuantitatif analitik observasional dengan pendekatan cross sectional yang terdiri dari dua siklus. Setiap siklus terdiri empat tahap, dimulai dari perencanaan tindakan, tindakan, observasi, dan refleksi. Subyek penelitian adalah siswa kelas 8I. Data diperoleh melalui wawancara tidak terstruktur, angket, dan soal kognitif. Teknik analisis data yang digunakan adalah deskriptif kualitatif.Hasil:Penelitian menunjukkan bahwa pemberian sosialisasi metode ceramah dapat meningkatkan; 1) hasil belajar kognitif secara klasikal dengan rata-rata ketercapaian 72% di siklus I menjadi 80% di siklus II atau dengan presentase ketuntasan kelas 71% di siklus I menjadi 100% di siklus II; 2) dapat meningkatkan hasil belajar afektif dengan presentase ketercapaian 76% di siklus I menjadi 79% di siklus II.Kesimpulan:Sosialisasi metode ceramah dapat meningkatkan pengetahuan siswa kelas 8I SMP Negeri 1 Grogol Sukoharjo ditinjau dari hasil belajar kognitif dan afektif siswa.Kata Kunci:cross sectional, sediaan serta label obat ISPA dan diare, peningkatan belajar afektif kognitif.